2019
DOI: 10.1037/cap0000156
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in psychiatric admissions to hospital.

Abstract: The objective of this study was to identify seasonal variations in mental health–related hospitalizations among children, adolescents, and adults using administrative health data. Hospital admission records from January 2004 to March, 2014 were sourced from the New Brunswick Discharge Abstract Database. Seasonality was measured using a cosinor model to estimate the phase, amplitude, and peak of seasonal variations in psychiatric admissions over the 12-month period from January through December. A general linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The seasonal pattern of adolescent hospitalizations was similar to that found in a Norwegian study, which reported a seasonal reduction of access to services in summer and an opposite increase in winter [33]. The presence of a seasonal pattern in the trend of hospitalizations for psychiatric disorders was already reported in a Canadian study, with the peak of hospitalizations mainly occurring in February for adolescents and in May for adults [34]. The seasonal trend of adolescent hospitalizations could be linked to stressful factors during the school period.…”
Section: Discussionsupporting
confidence: 85%
“…The seasonal pattern of adolescent hospitalizations was similar to that found in a Norwegian study, which reported a seasonal reduction of access to services in summer and an opposite increase in winter [33]. The presence of a seasonal pattern in the trend of hospitalizations for psychiatric disorders was already reported in a Canadian study, with the peak of hospitalizations mainly occurring in February for adolescents and in May for adults [34]. The seasonal trend of adolescent hospitalizations could be linked to stressful factors during the school period.…”
Section: Discussionsupporting
confidence: 85%
“…We found three prospective cohort studies, which measured academic pressure at baseline and mental health at follow-up (follow-up ranged from one to five years) (Fu et al, 2022; Kaman et al, 2021; Torsheim et al, 2003). A further prospective cohort study investigated how mental health outcomes differed according to proximity to examinations (Locker and Cropley, 2004) We found nine longitudinal studies that used a time series design, where data were collected from mental health services or administrative records, to assess associations between mental health service use or outcomes and timing within the year (Blackburn et al, 2021; Carbone et al, 2019; Hansen and Lang, 2011; Hawton et al, 2003; Lahti et al, 2007; Matsubayashi et al, 2016; McCleary et al, 1991; Slaunwhite et al, 2019; Spiller et al, 2020). Sample sizes were generally large, with 34 studies containing over 1,000 participants.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of Canadian adolescents, mental health-related hospital admissions were found to be highest from January to April, and in October and November and lowest during periods of school closure in July, August and December (Slaunwhite et al, 2019). In a study of stress-related emergency hospital admissions in England, admissions were highest for adolescents during term-time and lowest during school holidays (Blackburn et al, 2021).…”
Section: Resultsmentioning
confidence: 99%